2008
DOI: 10.3748/wjg.14.3927
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal metastasis of hepatocellular carcinoma after spontaneous rupture: A case report

Abstract: INTRODUCTIONHepatocellular carcinoma (HCC) is one of the most common malignancies worldwide. It is usually manifested in the 6th and 7th decades of life. Extrahepatic metastases are seen in 64% of patients with HCC. The most frequent sites of extrahepatic metastases are lung, abdominal lymph node and bone, but peritoneal dissemination is unusual [1,2] . The incidence of spontaneous rupture of HCC is about 8%-26% in Asia [3][4][5] and the mortality rate of HCC patients is 10% [6] . However, peritoneal metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 35 publications
2
27
1
1
Order By: Relevance
“…Peritoneal metastasis from HCC is rare, but tumor implantation on the peritoneal surfaces occurs after HCC rupture (17,(23)(24)(25)(26)(27)(28). Our results showed that peritoneal implantation after HCC rupture was not rare.…”
Section: Discussioncontrasting
confidence: 44%
“…Peritoneal metastasis from HCC is rare, but tumor implantation on the peritoneal surfaces occurs after HCC rupture (17,(23)(24)(25)(26)(27)(28). Our results showed that peritoneal implantation after HCC rupture was not rare.…”
Section: Discussioncontrasting
confidence: 44%
“…Intraperitoneal metastases are rare but their risk is elevated in tumor rupture. If the peritoneal implant is unique, which is the most common form of presentation, the treatment of choice is resection (4,5). The singularity of the case described here is the debut as acute hemoperitoneum together with multiple peritoneal dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Another suggested mechanism is that rupture of exophytic HCC into the peritoneal cavity can cause subsequent seeding of a metastatic deposit. This was only suggested in several case studies and a small number of clinical studies [7,[10][11][12][13][14]. Therefore, we still do not know exactly whether percutaneous procedures or HCC rupture are risk factors of PM in HCC patients.…”
Section: Introductionmentioning
confidence: 96%